2018
DOI: 10.1038/s41589-018-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional TRIM24 degrader via conjugation of ineffectual bromodomain and VHL ligands

Abstract: The addressable pocket of a protein is often not functionally relevant in disease. This is true for the multidomain, bromodomain-containing transcriptional regulator TRIM24. TRIM24 has been posited as a dependency in numerous cancers, yet potent and selective ligands for the TRIM24 bromodomain do not exert effective anti-proliferative responses. We therefore repositioned these probes as targeting features for heterobifunctional protein degraders. Recruitment of the VHL E3 ubiquitin ligase by dTRIM24 elicits po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 51 publications
(54 reference statements)
3
163
0
2
Order By: Relevance
“…The predicted inhibition of TRIM24 would, therefore, be consistent with a dominant Th1 type immune response during murine EVL. TRIM24 is also observed as a target for inactivation during infection with lab-adapted H1N1influenza A virus 70 and has been shown to be targetable using novel heterobifunctional protein degraders 71 , suggesting that pathways controlled by TRIM24 could be further manipulated in favour of host protection. …”
Section: Discussionmentioning
confidence: 99%
“…The predicted inhibition of TRIM24 would, therefore, be consistent with a dominant Th1 type immune response during murine EVL. TRIM24 is also observed as a target for inactivation during infection with lab-adapted H1N1influenza A virus 70 and has been shown to be targetable using novel heterobifunctional protein degraders 71 , suggesting that pathways controlled by TRIM24 could be further manipulated in favour of host protection. …”
Section: Discussionmentioning
confidence: 99%
“…47 The effects of PROTACs-based on BETi, ARV-825, and ARV-771 The group reported that their PROTACs specifically decreased BRD4 downstream genes, including c-MYC and N-MYC. 76 This again encouraged to search for new path to undruggable targets. 73 They finally showed that PROTACs were able to induce a rapid loss of viability of primary cells from myeloma patients and inhibited the growth of MM1.S-based xenografts in mouse.…”
Section: Targeting Nuclear Receptorsmentioning
confidence: 99%
“…75 A recent study extended designs of PROTACs against TRIM24, another bromodomain-containing transcriptional regulator. 76 This again encouraged to search for new path to undruggable targets.…”
Section: Targeting Transcriptional Regulators Bet Family Proteinsmentioning
confidence: 99%
“…Bradner and co‐workers disclosed dTRIM24 ( 84 ), the first TRIM24 PROTAC and degrader (Figure ) . Starting from a derivative of previously reported dual TRIM24/BRPF chemical probe IACS‐9571 ( 80 ), a VHL E3 ligase inhibitor was appended via a PEG linker to create bifunctional molecule 84 which displayed similar potency to TRIM24 inhibitor 83 .…”
Section: Typical Non‐bet Bromodomain Inhibitorsmentioning
confidence: 99%
“…Bradner and co-workers disclosed dTRIM24 (84), the first TRIM24 PROTAC and degrader ( Figure 13). [106] Startingf rom a derivativeo fp reviously reported dual TRIM24/BRPF chemical probe IACS-9571 (80), aV HL E3 ligase inhibitor was appended via aP EG linker to create bifunctional molecule 84 which displayed similar potency to TRIM24 inhibitor 83.L ikewise, as imilar selectivity profile was observed for 84 against ap anel of 32 bromodomains, with equipotency showna gainst BRPF1 and BRPF2.C ellular permeability was also demonstrated via aV HL degron displacementa ssay,p roviding evidence of target engagement. Importantly, 84 was shown to solely degrade TRIM24 (despite selectivity concerns with BRPF1/2) substantially at 4hours and degradation wasm aintained over 72 hours.…”
Section: Trim24mentioning
confidence: 99%